Critical Analysis of Sharpe, Treynor and Jensen Methods in Analyzing Stock Portfolio Performance LQ-45 Stock Studies - Qur'anitasari Qur'anitasari; Nila Firdausi Nuzula; Ari Darmawan (APMBA (Asia Pacific Management and Business Application), 2019)
The purpose of this study is to determine the stocks of the LQ-45 Index which form a portfolio based on a single index model, analyzed by Sharpe, Treynor, and Jensen methods, whether there are differences in the results of calculations and which is the most appropriate in measuring portfolio performance. The method used in this research is descriptive research with a quantitative approach and the data source used is secondary data from the Indonesia Stock Exchange. The population used is the LQ-45 Index shares for the period 2013-2018 and based on established criteria, a sample of 22 shares was obtained. Based on the methods of Sharpe, Treynor, and Jensen, the portfolio performance that is formed experiences a similar and fluctuating movement. Because the three methods produce almost the same value movement, the determination of slope (linear curve) requires accuracy, therefore re-testing is done by using Robustness Test. With the regression analysis it shows that the Sharpe method is most appropriate to be used in measuring portfolio performance in this study. Researchers suggest for further research, in the formation of portfolios can use other portfolio formation models. This research in the formation of LQ-45 stock portfolios using the single index model method, the portfolio formed is only one portfolio each year which causes less number of portfolios compared. In addition to the Sharpe, Treynor, and Jensen methods, researchers can then use other performance measurement methods for comparisons, such as M2 (Modigliani-Modigliani) and Information Ratio (RI).